2016
DOI: 10.1021/acscombsci.5b00146
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of Chemical Beam Vapor Deposition System for Efficient Combinatorial Investigations of Thin Oxide Films: Deposited Film Properties versus Precursor Flow Simulations

Abstract: An innovative deposition system has been developed to construct complex material thin films from single-element precursors by chemical beam vapor deposition (CBVD). It relies on well distributed punctual sources that emit individually controlled precursor beams toward the substrate under high vacuum conditions combined with well designed cryo-panel surfaces that avoid secondary precursor sources. In this configuration the impinging flows of all precursors can be calculated at any substrate point considering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 82 publications
2
20
0
Order By: Relevance
“…In the present work, we report on Chemical Beam Vapour Deposition (CBVD) of high optical quality Si:TiO 2 film whose amorphous state is preserved by doping with silicon [20]. The amorphisation of deposited TiO 2 with Si doping was already reported [21], and a more recent detailed study of amorphisation of Nb:TiO 2 thin films by doping with Si is reported elsewhere [22]. Even though this doping leads to a slight decrease in the refractive index of the film, in agreement with results achieved with other Chemical Vapour deposition techniques [23], the index is still high enough to support waveguiding on highindex optical crystals such as YAG and sapphire.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In the present work, we report on Chemical Beam Vapour Deposition (CBVD) of high optical quality Si:TiO 2 film whose amorphous state is preserved by doping with silicon [20]. The amorphisation of deposited TiO 2 with Si doping was already reported [21], and a more recent detailed study of amorphisation of Nb:TiO 2 thin films by doping with Si is reported elsewhere [22]. Even though this doping leads to a slight decrease in the refractive index of the film, in agreement with results achieved with other Chemical Vapour deposition techniques [23], the index is still high enough to support waveguiding on highindex optical crystals such as YAG and sapphire.…”
Section: Introductionmentioning
confidence: 85%
“…Oxide thin films were deposited by CBVD, as described in detail elsewhere [21]. The CBVD process makes use of thermal decomposition of organometallic precursors on a heated substrate in a high vacuum environment (≤ 10 −3 Pa).…”
Section: Deposition Of Si:tio 2 Combinatorial Filmmentioning
confidence: 99%
“…The depositions were carried out in a CBVD system able to accommodate a 450 mm diameter substrate (Sybilla-450, ABCD Technology, Ferney-Voltaire, France). A similar equipment (Sybilla 150) and the operating mode of this technique are described elsewhere [ 26 ]. Substrate heating is achieved by a graphite heating system radiatively heating the substrate up to 800 °C.…”
Section: Methodsmentioning
confidence: 99%
“…A multitude of combinatorial configurations are achievable with the possibility to obtain a wide range of flow compositions from the different precursors across the deposition area. In Sybilla equipment [ 26 ], the amount of each precursor reaching a given position of the substrate can, thus, be finely controlled and predicted by accurate calculations, enabling stoichiometry tuning. In addition to negligible gas phase collisions, CBVD has some further peculiarities compared to traditional CVD at higher pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation